2019
DOI: 10.1152/ajpregu.00075.2018
|View full text |Cite
|
Sign up to set email alerts
|

Gestational hypertensive disorders show unique patterns of circulatory deterioration with ongoing pregnancy

Abstract: A combined assessment of heart, arteries, veins, and body fluid content throughout pregnancy has not yet been reported. We hypothesized that a gradual aggravation of circulatory dysfunction exists from the latent to the clinical phase of gestational hypertensive disease (GHD), and that pathways are unique for preeclampsia with early onset < 34 wk (EPE) and late onset ≥ 34 wk (LPE), and gestational hypertension (GH). Women with singleton pregnancy and no known diseases were invited for a prospective, observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 67 publications
1
39
0
4
Order By: Relevance
“…The second type of late PE presents with high cardiac output throughout all stages of pregnancy, minimal signs of endothelial activation, and has been reported in a population of © 2020 Nordic Federation of Societies of Obstetrics and Gynecology WG and JL contributed equally as first authors mainly obese women 13. Abnormal Doppler ultrasound of the maternal renal interlobar and hepatic veins has been reported in different types of PE, but not in gestational hypertension 8. These patterns are consistent with retrograde induction of maternal organ dysfunction due to congestion, caused by either increased venous vascular tone and intravenous hypertension, or by volume stasis following (sub-)obstructed venous drainage and external venous compression.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…The second type of late PE presents with high cardiac output throughout all stages of pregnancy, minimal signs of endothelial activation, and has been reported in a population of © 2020 Nordic Federation of Societies of Obstetrics and Gynecology WG and JL contributed equally as first authors mainly obese women 13. Abnormal Doppler ultrasound of the maternal renal interlobar and hepatic veins has been reported in different types of PE, but not in gestational hypertension 8. These patterns are consistent with retrograde induction of maternal organ dysfunction due to congestion, caused by either increased venous vascular tone and intravenous hypertension, or by volume stasis following (sub-)obstructed venous drainage and external venous compression.…”
supporting
confidence: 60%
“…7 When this volume load is superimposed on early gestational maternal cardiovascular dysfunction, hypertensive disorders of pregnancy may be induced through type-specific pathways. 8 Today, ongoing research into maternal hemodynamics has identified different types of PE. Early-onset preeclampsia presents in the first trimester with increased vascular tone, a modest rise in cardiac output, and reduced plasma volume expansion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, different phenotypes of PE have been identified according to maternal hemodynamic characteristics [40]. PE with fetal growth restriction is known as a hypertonic state with a low cardiac output and a high vascular resistance circulation, presenting predominantly before 34 weeks of gestation, and therefore, often referred to as early-onset PE (EPE) [41,42]. PE with normal fetal growth is characterized as a hypervolemia circulation with normal to high cardiac output and normal to low vascular resistance, usually presenting near term, and thus, commonly labelled as late-onset PE (LPE) [41][42][43][44][45].…”
Section: Increase In Iap During Pregnancy Might Induce Venous Congestmentioning
confidence: 99%
“…The indexing of cardiac output is limited by the fact that body surface area may not accurately reflect the metabolic demands of increased body mass, but at present no other method of indexing is available and such indexing remains the best way of understanding whether cardiac output is appropriate for maternal body size in pregnancy. Indexing cardiac output may be an approximating process but provides a better understanding of the underlying pathophysiology, which demonstrates that early preeclampsia is characterised by lower maternal cardiac output, while late preeclampsia is associated with normal or lowered cardiac output compared to normal controls (Buddeberg et al 2018a;Gyselaers et al 2019). The severity and temporal nature of cardiovascular dysfunction in early and late preeclampsia provides important insights into the pathophysiology of the disorder.…”
Section: Cardiorenal Interactions and Their Effect On Placental Permentioning
confidence: 99%